2011
DOI: 10.1007/s13580-011-0007-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the protective antigen for PEDV in transgenic duckweed, Lemna minor

Abstract: Duckweeds are small, floating aquatic plants with a number of useful characteristics, including edibility, fastgrowing, and a clonal proliferation. Duckweed is also fed to animals as a diet complement because of its high nutritional value. Porcine epidemic diarrhea virus (PEDV) is a major causative agent of fatal diarrhea in piglets and is a serious problem in the hog-raising industry. In this study, we assessed the feasibility of producing a protective antigen for the PEDV spike protein 1 using duckweed, Lemn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…In comparison to previous Agrobacterium ‐mediated transformation protocols in L. minor (Cantó‐Pastor et al ., ; Chhabra et al ., ; Firsov et al ., , ; Ko et al ., ; Sun et al ., ; Yamamoto et al ., ; Yang et al ., , , ), the increased efficiency of our protocol is likely resulted from adopting sonication coupled with vacuum infiltration infection method. In several previous studies, such as banana (Subramanyam et al ., ), chickpea (Indurker et al ., ) and cowpea (Bakshi et al ., ), it has been shown that the combination of vacuum infiltration and sonication can greatly improve the efficiency of Agrobacterium infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to previous Agrobacterium ‐mediated transformation protocols in L. minor (Cantó‐Pastor et al ., ; Chhabra et al ., ; Firsov et al ., , ; Ko et al ., ; Sun et al ., ; Yamamoto et al ., ; Yang et al ., , , ), the increased efficiency of our protocol is likely resulted from adopting sonication coupled with vacuum infiltration infection method. In several previous studies, such as banana (Subramanyam et al ., ), chickpea (Indurker et al ., ) and cowpea (Bakshi et al ., ), it has been shown that the combination of vacuum infiltration and sonication can greatly improve the efficiency of Agrobacterium infection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, duckweeds are capable of rapidly accumulating heavy metals, nutrients and pollutants, which can be used for bio‐remediation of wastewater (Cheng and Stomp, ; Khellaf and Zerdaoui, ; Megateli et al ., ; Stout et al ., ; Xu et al ., ). The extremely fast population doubling rate (3–5 days per asexual doubling under ideal conditions) also makes duckweeds a good candidate for the production of recombinant proteins including antigens, monoclonal antibodies and exogenous enzymes (Cox et al ., ; Firsov et al ., , ; Khvatkov et al ., ; Ko et al ., ; Naik et al ., ; Stomp, ; Sun et al ., ), as well as dietary supplements for humans and animals because of its high nutritional value (Appenroth et al ., ; Beukelaar et al ., ; Bhanthumnavin and Mcgarry, ). Despite the potential for both basic research and industrial applications that established duckweeds as one of the most promising alternative future crops (Appenroth et al ., ; Lam et al ., ), current research and development in duckweeds are constrained by the lack of efficient genetic manipulation tools that allow to knockout or knock‐in a gene of interest in the duckweed genome within a short time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several duckweed species, e.g. Lemna minor, have been engineered to produce antigens, monoclonal antibodies and exogenous enzymes (Sun et al 2007;Ko et al 2011;Naik et al 2012). Additionally, duckweed can be used as a dietary supplement for humans and animals because of its high nutritional value (Bhanthumnavin & Mcgarry 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Several commercially important proteins have already been successfully expressed in duckweed plants: the endoglucanase E1 from Acidothermus cellulolyticus (Sun et al, 2007 ), and monoclonal antibodies against CD20, CD30, and interferon α2b (Cox et al, 2006 ). Protective antigen of swine epidemic diarrhea (Ko et al, 2011 ), tuberculosis antigens ESAT6 and Ag85B (Peterson et al, 2015 ), and hemagglutinin of avian influenza virus H5N1 (Bertran et al, 2015 ; Huong et al, 2015 ) have also been successfully expressed in these plants.…”
Section: Introductionmentioning
confidence: 99%